Hubungan Beban Kerja Perawat Dengan Kelengkapan Pendokumentasian Asuhan Keperawatan Di Ruang Rawat Inap Infeksi Dan Non Infeksi RSUD dr. Murjani Sampit - Putria Carolina; Melisa Frisilia; Diana Oktavia (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Professional nurses are confronted with the demand for responsibility and accountability in every action they take. The workload of nurses is extensive when providing nursing care. Documentation is considered complete if the recording is done according to hospital standards. The phenomenon that occurs is that some reasons become obstacles for nurses, including the large amount of documentation that needs to be written and filled out, sometimes overwhelming nurses. Additionally, the imbalance between nurses and patients, specific rooms are always full of patients while the number of nurses on duty is insufficient. As a result, there is a risk of a decrease in the quality of documentation, affecting the accuracy and completeness of nursing records. The aim of this study is to determine the relationship between the workload of nurses and the completeness of nursing care documentation in the infectious and non-infectious inpatient room of RSUD dr. Murjani Sampit. This study uses a correlational design with a cross-sectional approach. The Simple Random Sampling technique was used with a total of 57 respondents. Based on the Chi-Square test results, the p-value obtained is 0.000 or the significance level of p < 0.05, thus Ha is accepted. The conclusion of the study is that there is a relationship between the workload of nurses and the completeness of nursing care documentation in the infectious and non-infectious inpatient rooms of RSUD dr. Murjani Sampit. It is hoped that nurses can improve their nursing performance in providing holistic nursing care and record it in writing according to the nursing care format.